Hypercalcaemia due to calcium binding IgM paraprotein in Waldenström's macroglobulinaemia. Issue 10 (October 1995) - Side, L; Fahie-Wilson, M N; Mills, M J
Abstract : A case of Waldenström's macroglobulinaemia with asymptomatic hypercalcaemia is reported in which calcium binding to the paraprotein was found. This is the first report of this phenomenon in Waldenström's macroglobulinaemia and the first report of calcium binding to an IgM paraprotein.